Case Report: Assessment Of A Patient Diagnosed With Osler Weber Rendu According To Abdellah's 21 Nursing Problems Model - Ilknur Yücel (Health and Technology Journal (HTechJ), 2023)
In this case report, a patient diagnosed with "Osler Weber Rendu" was examined based on Faye Abdellah's "21 Nursing Problem Theory". It aimed to prepare a nursing care plan for the patient using the nursing diagnoses in the North American Nurses Diagnosis Association (NANDA) classification system. The patient is a 51-year-old single female. The patient, who is a high school graduate and retired, lives in a metropolitan area and has never smoked or consumed alcohol in her entire life. The patient was diagnosed with iron deficiency anemia in 2016 and applied to a city hospital in 2017 due to the deepening of postmenopausal anemia, nosebleeds and as a result of the examinations, angiodysplasia was detected on the gastric corpus, duodenum, ileocecal valve and she was diagnosed with Osler-Weber-Rendu. 2019 the patient was diagnosed with Papillary Thyroid Cancer in the external center. Patient care is very important in the nursing profession. It was observed that planning the patient's care according to Abdellah's 21 Nursing Problem Model and analyzing the data according to the sub-dimensions of the model solved the patient's problems in a short time and the nursing care given to the patient was systematic.